Cold plasma hydrophilization of soy protein isolate and milk protein concentrate enables manufacturing of surfactant-free water suspensions. Part I: Hydrophilization of food powders using cold plasma. (August 2021) - Bormashenko, Edward; Bormashenko, Yelena; Legchenkova, Irina; Eren, Necla Mine
Abstract: In this study, we found that treatment with cold plasma influenced the wetting properties of soy protein isolate and milk protein concentrate powders. Cold plasma treatment significantly decreased the apparent contact angle of the powders, indicating hydrophilization of the powders. Cold radiofrequency low-pressure plasma treatment had a larger effect on powder wettability than corona atmospheric plasma discharge. In addition, cold plasma treatment had a more noticeable effect on the wettability of the hydrophobic milk protein concentrate than on the inherently hydrophilic soy protein isolate. Both the soy protein isolate and milk protein concentrate demonstrated zero hydrophobic recovery over time. Scanning electron microscopy showed that cold air plasma treatment of food powders caused minor surface oxidation, though these changes were not observed using FTIR spectroscopy. We suggest that cold plasma treatment has important implications for the production of stabilizer-free food suspensions. Highlights: Cold plasma treatment influenced wetting of the soy protein isolate and milk protein concentrate. Hydrophilization of the food powders is attained by the cold plasma treatment. Hydrophilization of the hydrophobic milk protein concentrate was more pronounced. The studied powders demonstrated zero hydrophobic recovery. Cold air plasma treatment of food powders led to their minor surface oxidation. The IR-spectroscopy did not reveal the change in the chemical composition of the powders.